2022
DOI: 10.1021/acsnano.1c05505
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibition in GBM Primed with Radiation by Engineered Extracellular Vesicles

Abstract: The lack of safe and effective delivery across the blood-brain barrier and the profound immune suppressive microenvironment are two main hurdles to glioblastoma (GBM) therapies. Extracellular vesicles (EVs) have been used as therapeutic delivery vehicles to GBM but with limited efficacy. We hypothesized that EV delivery to GBM can be enhanced by (i) modifying the EV surface with a brain-tumor-targeting cyclic RGDyK peptide (RGD-EV) and (ii) using bursts of radiation for enhanced accumulation. In addition, EVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 59 publications
0
60
0
Order By: Relevance
“…The immune activity and stromal activity were remarkably elevated in the high-risk group, which once again reiterated the heterogeneity of the glioma TIME between the two groups. Determining the roles of the signature genes in TIME cell infiltration heterogeneity will be beneficial to better understand the mechanisms of the TIME antitumor immune response and developing novel immunotherapy strategies ( Kim et al, 2022 ; Ogino et al, 2022 ; Tian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immune activity and stromal activity were remarkably elevated in the high-risk group, which once again reiterated the heterogeneity of the glioma TIME between the two groups. Determining the roles of the signature genes in TIME cell infiltration heterogeneity will be beneficial to better understand the mechanisms of the TIME antitumor immune response and developing novel immunotherapy strategies ( Kim et al, 2022 ; Ogino et al, 2022 ; Tian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In glioblastoma, overcoming the TME physical barrier is also being explored. One group combined brain-tumor-targeted peptide-coated extracellular vesicles, loaded with small interfering RNA (siRNA) against PD-L1, and then delivered them with bursts of radiation therapy [ 194 ]. Dual inhibition of PI3K/mTOR pathway combined with the microtubule targeting chemotherapy, paclitaxel, along with ICI, induced sustainable DC, T cell and NK responses, both locally in the TME and systemically [ 195 ].…”
Section: Basic Research In Cancer Immunologymentioning
confidence: 99%
“…Furthermore, RT has the potential to alter the immune environment and sensitize less immunogenic tumors to ICB. RVG-engineered exosomes (RGD-EV) was developed to deliver siRNA against PD-L1 to GBM (Tian et al, 2022). The results showed that short pulse radiation significantly improved the targeting efficiency of RGD-EVs to brain tumors and their micro-environment, and effectively attenuated radiation-induced tumor-associated myeloid cells and PD-L1 expression on tumor cells.…”
Section: Targeting Immunosuppressive Microenvironmentmentioning
confidence: 99%